COMMUNITY ETHICS IN THE NEW BEHAVIOR ORDER IN THE PERSPECTIVE OF SOCIAL STUDIES EDUCATION - Ajeng Ginanjar; Dena Yemin Meisendi (Sean Institute, 2023)
The world health agency (WHO) has declared Covid-19 a pandemic. The latest data reported by WHO until April 6, 2023, there are 762 million cases with 6.8 million deaths worldwide. Meanwhile, in Indonesia, there were around 6.7 positive cases of COVID-19 and 161 thousand cases of death. Based on this data, we can see that the coronavirus has become a severe threat to the world's population. Unsurprisingly, various efforts have yet to be made to tackle this epidemic. The latest data update at the beginning of 2023, Covid cases have decreased, but of course, it does not necessarily make us arbitrary in maintaining our health. There needs to be commitment and discipline from all elements of society in implementing health protocols as a form of post-pandemic societal ethics. This is our initial capital in living in a new order of behavior (New Normal). Social studies education plays a role as part of the educational guard in shaping students' societal ethics according to the times' needs. With their innovative competencies, open-mindedness towards change, and noble responsibilities in the profession they carry out, social studies teachers should be motivated by this development. IPS experts, with all their scientific potential, will continue to be able to flow fresh ideas to IPS in responding to today's challenges, both vertically and horizontally. His openness to change, as well as his noble responsibility to the profession, carried out, should be motivated by this development. IPS experts, with all their scientific potential, will continue to be able to flow fresh ideas to IPS in responding to today's challenges, both vertically and horizontally. His openness to change, as well as his noble responsibility to the profession, carried out, should be motivated by this development. IPS experts, with all their scientific potential, will continue to be able to flow fresh ideas to IPS in responding to today's challenges, both vertically and horizontally